Direct minimally invasive intraoperative electrophysiological mapping of the heart. Issue 6 (December 2013) - Ando, Takehiro; Kawashima, Dai; Kim, Hongho; Joung, Sanghyun; Liao, Hongen; Kobayashi, Etsuko; Gojo, Satoshi; Kyo, Syunei; Ono, Minoru; Sakuma, Ichiro
Abstract Introduction: Cardiac electrophysiology aims to describe and treat the electrical activity of the heart. Although an epicardial approach is valuable in many surgical treatments such as coronary artery bypass grafting, maze ablation, and cell transplantation, very few techniques suited for minimally invasive surgery are available for measurement of epicardial electrophysiology. Material and methods: We developed a novel endoscopically-deployable expanding electrode array that can be applied for minimally invasive surgery. Our device consists of a flexible electrode array attached to arms which open and close the electrode sheet. Furthermore, we also developed a computer program to overlay an epicardial electrophysiological map on an endoscopic image. We performed both laboratory and in vivo experiments to examine the feasibility in clinical situations. Results: Evaluation experiments demonstrated that our novel mapping process that assumes spherical deformation of the electrode array enables us to overlay each electrode position with an accuracy of < 1 mm. Results of animal experiments using large animals (one dog and two pigs) demonstrated that our system enables construction of epicardial electrophysiological maps. Conclusion: A novel endoscopically deployable expanding electrode array was developed. Evaluation experiments demonstrated that our device can be manipulated in simulated minimally invasive surgery, and enables construction of epicardial electrophysiological maps.